2022
DOI: 10.28945/4982
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Relationship of Social/Emotional, Cognitive, and Behavioral Engagements on Developing Preservice Teachers’ Digital Competencies

Areej ElSayary,
Laila Mohebi,
Lawrence Meda

Abstract: Aim/Purpose: This study investigates the impact of the relationship between social/emotional, cognitive, and behavioral engagements on developing preservice teachers’ digital competencies. The social/emotional engagement can be illustrated with actions associated with learning, such as excitement, interest, and motivation. Cognitive engagement is the active process of learning and is the most essential form of learning. Finally, behavioral engagement is the physical behavior associated with doing the work and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In this study, digital literacy has a positive and significant effect on student involvement in hybrid learning which is expressed with CR values of 3,905 > 1.98. It is in line with research (Damrongpanit, 2022;ElSayary et al, 2022). These findings highlight the importance of mastering digital literacy can encourage increased access to learning resources more broadly and deeply through digital devices.…”
Section: Resultssupporting
confidence: 88%
“…In this study, digital literacy has a positive and significant effect on student involvement in hybrid learning which is expressed with CR values of 3,905 > 1.98. It is in line with research (Damrongpanit, 2022;ElSayary et al, 2022). These findings highlight the importance of mastering digital literacy can encourage increased access to learning resources more broadly and deeply through digital devices.…”
Section: Resultssupporting
confidence: 88%
“…Results showed that participants inaccurately assessed their digital competencies. ElSayary et al (2022) examined the impact of social/emotional, cognitive, and behavioral engagement on the development of digital literacy among preservice teachers. The study findings revealed a notable and favorable association between the engagement levels in social/emotional, cognitive, and behavioral aspects, which consequently contributed to the enhancement of digital literacy skills among pre-service teachers.…”
Section: / 10mentioning
confidence: 99%
“…Digital literacy is a key skill that students must have to face the increasingly advanced digital era (Anthonysamy, 2020;List, 2019). Technical, cognitive, and social-emotional factors are important aspects of digital literacy that influence how students interact with digital and information technologies (ElSayary et al, 2022;Nikou et al, 2018;Saleha et al, 2022). This research helps identify students' digital literacy levels and attitudes toward using technology in learning.…”
Section: Introductionmentioning
confidence: 99%